Thermal and Fluid Dynamic Behaviors of Confined Slot Jets Impinging on an Isothermal Moving Surface with Nanofluids - Bernardo Buonomo; Oronzio Manca; Nadezhda S. Bondareva; Mikhail A. Sheremet (Energies, 2019)
A two-dimensional numerical investigation of turbulent convective heat transfer due to a confined slot jet impinging on an isothermal moving surface is accomplished. The confined geometry has an upper adiabatic surface parallel to the heated moving plate and the slot jet is in the middle of the confining adiabatic wall. The working fluids are pure water or a nanofluid, which in this case was a mixture of water and Al2O3 nanoparticles. The governing equations are written adopting the k-ε turbulence model with enhanced wall treatment and the single-phase model approach for the nanofluids. The numerical model is solved using the finite volume method with the Ansys Fluent code. Two geometric configurations regarding two values of the jet distance from the target surface are considered in the simulations. The concentration of nanoparticles ranges from 0% to 6%, with a single diameter equal to 30 nm, Reynolds numbers ranging from 5000 to 20000, and a moving surface-jet velocity ratio between 0 and 2 are examined in the investigation. The aim is to study the system behaviors by means of local and average Nusselt numbers, local and average friction factor/skin friction factor, stream function, and temperature fields. Results show that the presence of nanoparticles determines an increase in the dimensionless heat transfer but, as expected, does not affect the friction factor. The local and average increase in Nusselt numbers is also due to a combined effect of the moving plate and nanofluids.